Pengaruh Kepemimpinan, Motivasi dan Lingkungan Kerja Terhadap Disiplin Kerja Pegawai Dinas Perindustrian dan Tenaga Kerja Kabupaten Sukoharjo - Kurniawan, Stiven Andi Wahyu; Handayani, Asih (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2025)
This research aims to understand the extent to which leadership, work motivation and work environment influence the level of work discipline of employees at the Sukoharjo Regency Industry and Manpower Service. This research involved all service employees, a total of 30 people, using a saturated sampling method. Data collection was carried out through questionnaires, then analyzed using a quantitative approach using SPSS version 25 software. The data analysis process included classical assumption tests, multiple linear regression, t test, F test (to test the feasibility of the model), and the coefficient of determination (R2) test. . The t test results show that leadership has a significant influence on work discipline with p-value = 0.030 < 0.05. Work motivation is also proven to have a significant influence on work discipline with p-value = 0.006 < 0.05, and the work environment has a significant influence on work discipline with p-value = 0.012 < 0.05.